KNOWLEDGE MANAGEMENT SYSTEM DEVELOPMENT TO IMPROVE CUSTOMER SERVICE QUALITY ON A CAKE SHOP - Faroqie, Haveiszal; Mey Jesika Rani, Monica; Nurwegiono, Muhammad (Universitas Ma Chung, 2025)
This study aims to develop a WordPress-based Knowledge Management System (KMS) to enhance customer service quality at